Feeding preference of Helicoverpa armigera larvae (Lepidoptera: Noctuidae) on vegetative and reproductive organs of soybean plants (Research, Society and Development, 2022)
Helicoverpa armigera is a pest insect with a large dispersal range, a high degree of polyphagy in the larval stage, and of difficult control. The pest's ability to survive due to the availability of food and persist in grain production systems present in several Brazilian regions allows it to infest a wide range of crops, including soybeans and invasive plants during the off-season. There is general knowledge that the larva prefers to feed on plant reproductive organs, but it is unknown if this is true for soybeans, a crop to which it is adapting following its recent recognition as a pest. Basic knowledge of herbivore feeding behavior is necessary to support control within the integrated pest management philosophy. The purpose of this study was to examine the preference behavior of H. armigera larvae in their first, fourth, and sixth instars for vegetative and reproductive organs of soybean plants. It is concluded that the larvae, regardless of instar, feed on all available vegetative and reproductive organs, but they have preferences based on their current developmental stage.